Body Awareness, Mindfulness and Affect: Does the Kind of Physical Activity Make a Difference? - Tihanyi, Benedek T.; Sági, Andrea; Csala, Barbara; Tolnai, Nóra; Köteles, Ferenc (European Journal of Mental Health, 2016)
The aim of this cross-sectional study is to explore expected differences in the connection between particular physical activities and positive and negative affect, body awareness or mindfulness. Additionally, we describe the so-called tingling phenomenon (i.e. skin-related sensations evoked by focusing on a body part) in terms of prevalence, gender differences and psychological concomitants. A total of 1,057 individuals (331 male; mean age: 30.6 ± 10.17 years) practicing yoga, Pilates training, kung fu, aerobic, or ballroom dance completed our questionnaire. Analysing data of all sports together, weekly frequency of practice, as opposed to time elapsed since starting practice, was connected to lower levels of negative affect and somatosensory amplification, and to higher levels of positive affect. Advanced yoga and Pilates participants showed higher body awareness; advanced kung fu participants amplified bodily signals the least, and aerobic was related to the highest positive affect. Among beginners, there were no practically relevant differences in the assessed constructs. These results might help to clarify the common and different psychological properties that are needed for and/or can be developed by different sports.